Dual functions of discoidinolysin, a cholesterol-dependent cytolysin with N-terminal discoidin domain produced from Streptococcus mitis strain Nm-76. Issue 1 (31st December 2022) - Tabata, Atsushi; Matsumoto, Airi; Fujimoto, Ai; Ohkura, Kazuto; Ikeda, Takuya; Oda, Hiroki; Yokohata, Shuto; Kobayashi, Miho; Tomoyasu, Toshifumi; Takao, Ayuko; Ohkuni, Hisashi; Nagamune, Hideaki
ABSTRACT: Background: Some strains of Streptococcus mitis exhibit β-hemolysis due to the β-hemolytic activity of cholesterol-dependent cytolysin (CDC). Recently, a gene encoding an atypical lectinolysin-related CDC was found in S. mitis strain Nm-76. However, the product of this gene remains uncharacterized. We aimed to characterize this atypical CDC and its molecular functions and contribution to the pathogenicity of S. mitis strain Nm-76. Methods: Phylogenetic analysis of the CDC gene was conducted based on the web-deposited information. The molecular characteristics of CDC were investigated using a gene-deletion mutant strain and recombinant proteins expressed in Escherichia coli . Results: The gene encoding CDC found in Nm-76 and its homolog are distributed among many S. mitis strains. This CDC is phylogenetically different from other previously characterized CDCs, such as S. mitis -derived human platelet aggregation factor (Sm-hPAF)/lectinolysin and mitilysin. Because this CDC possesses an additional N-terminal domain, including a discoidin motif, it was termed discoidinolysin (DLY). In addition to the preferential lysis of human cells, DLY displayed N-terminal domain-dependent facilitation of human erythrocyte aggregation and intercellular associations between human cells. Conclusion: DLY functions as a hemolysin/cytolysin and erythrocyte aggregation/intercellular association molecule. This dual-function DLY could be an additional virulence factor in S. mitis .